A degradable form of polyoma small T antigen reveals the high specificity of TAZ in regulating gene expression - Yubao Wang; Cherubin Manokaran; Kevin Huang; Brian Schaffhausen; Thomas M. Roberts (Proceedings of the National Academy of Sciences, 2025)
The study of DNA tumor viruses has revolutionized cancer biology, partly by virtue of the unique capabilities of viral oncoproteins to manipulate key proteins and pathways involved in tumorigenesis. We find a high affinity and selective binding of the polyoma small T antigen (PyST) with the transcription cofactor TAZ. By engineering a degradable version of PyST, we demonstrate that, when TAZ activity is modulated by PyST, a surprisingly small number of genes have altered expression and thus are candidate transcription targets of TAZ. Notably, knocking out TAZ, or its target genes CTGF or CYR61, abolishes the growth-promoting properties of PyST that are evident upon growth factor withdrawal. Therefore, by controlling the protein abundance of PyST and consequently TAZ activity, we find that TAZ is a transcriptional coactivator that can achieve important biological effects by acting on a limited number of gene targets.